Enhancing Community Knowledge and Attitudes toward Organic Liquid Fertilizer Production through Participatory Training in Nagari Paninjauan, X Koto District, Tanah Datar Regency - Fitri Amelia; Faizah Qurata’aini; Fazila Amelia; Kiki Amelia; Syamsi Aini; Iryani Iryani; Eka Yusmaita (Fakultas MIPA Universitas Negeri Padang, 2025)
Nagari Paninjauan, located on the slopes of Mount Marapi in West Sumatra, faces significant agricultural challenges, particularly due to rising chemical fertilizer costs, which affect productivity and farmers' welfare. High dependency on chemical fertilizers has also harmed soil health and the environment. To address this, a community service team from UNP held a training on producing organic liquid fertilizer (POC) tailored for various plant growth stages, such as soil enhancement, vegetative, and generative phases, as well as making organic growth regulators, fungicides, and insecticides. The training included material presentation, hands-on practice, and application in farming fields. Results showed participants’ understanding of POC production rose from 43.8% to 86.7%, and awareness of agricultural waste’s economic value also improved. Although the training effectively increased farmers' skills in independently producing POC, further strategies are needed to enhance understanding of technical materials for greater environmental and economic impact. Keywords —Organic Liquid Fertilizer (POC), Sustainable Farming, Agricultural Waste Utilization, Chemical Fertilizer Dependency, Community Training